Giải hệ pt sau = phương pháp thế:
a, \(\left\{{}\begin{matrix}\dfrac{x}{2}-\dfrac{y}{3}=1\\5x-8y=3\end{matrix}\right.\)
b, \(\left\{{}\begin{matrix}3x+2y=2\\6x-3y=18\end{matrix}\right.\)
giải hpt sau
\(\left\{{}\begin{matrix}3x^2+6xy-x+3y=0\\4x-9y=6\end{matrix}\right.\)
\(\left\{{}\begin{matrix}x^2+y^2-2x-2y-23=0\\x-3y-3=0\end{matrix}\right.\)
Giải các hệ phương trình sau:
a) \(\left\{{}\begin{matrix}2\left(x+1\right)-3y=-10\\3x+2y+5=0\end{matrix}\right.\)
b) \(\left\{{}\begin{matrix}\dfrac{x+1}{2}-\dfrac{y-2}{3}=1\\4x+3y=1\end{matrix}\right.\)
Giải các hệ phương trình:
a)\(\left\{{}\begin{matrix}\dfrac{x}{y}=\dfrac{2}{3}\\x+y-10=0\end{matrix}\right.\)
b)\(\left\{{}\begin{matrix}\left(3x+2\right)\left(2y-3\right)=6xy\\\left(4x+5\right)\left(y-5\right)=4xy\end{matrix}\right.\)
c)\(\left\{{}\begin{matrix}\left(2x-3\right)\left(2y+4\right)=4x\left(y-3\right)+54\\\left(x+1\right)\left(3y-3\right)=3y\left(x+1\right)-12\end{matrix}\right.\)
d)\(\left\{{}\begin{matrix}\dfrac{2y-5x}{3}+5=\dfrac{y+27}{4}-2x\\\dfrac{x+1}{3}+y=\dfrac{6y-5x}{7}\end{matrix}\right.\)
\(\left\{{}\begin{matrix}x^2+y^2+2x+4y=8\\\left(x+2y+1\right)\left(9+3y^2+4xy\right)=64\end{matrix}\right.\)
Giải các hệ phương trình sau:
a) \(\left\{{}\begin{matrix}2x+5y=5\\3x-5y=-30\end{matrix}\right.\) b) \(\left\{{}\begin{matrix}4x-3y=-5\\3x+2y=-8\end{matrix}\right.\)
c) \(\left\{{}\begin{matrix}3x+3y=9\\4x-2y=-2\end{matrix}\right.\) d) \(\left\{{}\begin{matrix}5x-4y=32\\6x+2y=18\end{matrix}\right.\)
e) \(\left\{{}\begin{matrix}2x-3y+5=0\\3x+5y-21=0\end{matrix}\right.\) f) \(\left\{{}\begin{matrix}x-y\sqrt{2}=0\\2x\sqrt{2}+y=5\end{matrix}\right.\)
g) \(\left\{{}\begin{matrix}5x+4y=-3\\3x+2y=11\end{matrix}\right.\) h) \(\left\{{}\begin{matrix}2x-4y=12\\5x+3y=17\end{matrix}\right.\)
\(\left\{{}\begin{matrix}4x^2+7xy+3y^2=0\\x^2+4x-y=6\end{matrix}\right.\) giải hệ pt sau
giải hệ phương trình
a
\(\left\{{}\begin{matrix}x+y=1\\x-y=-5\end{matrix}\right.\)
b.
\(\left\{{}\begin{matrix}2x+2y=5\\x-2y=1\end{matrix}\right.\)
c.
\(\left\{{}\begin{matrix}2x+3y=5\\3x-2y=1\end{matrix}\right.\)
Giải hệ \(\left\{{}\begin{matrix}\sqrt{x^2+2y+3}+2y-3=0\\2\left(2y^3+x^3\right)+3y\left(x+1\right)^2+6\left(x+1\right)+2=0\end{matrix}\right.\)